The effect of a weight gain prevention intervention on moderate-vigorous physical activity among black women: the Shape Program - Mary L. Greaney; Sandy Askew; Sherrie F. Wallington; Perry B. Foley; Lisa M. Quintiliani; Gary G. Bennett (BMC, 2017)
Abstract Background Rates of physical inactivity are high among Black women living in the United States with overweight or obesity, especially those living in the rural South. This study was conducted to determine if an efficacious weight gain prevention intervention increased moderate-vigorous physical activity (MVPA). Methods The Shape Program, a weight gain prevention intervention implemented in community health centers in rural North Carolina, was designed for socioeconomically disadvantaged Black women with overweight or obesity. MVPA was measured using accelerometers, and summarized into 1- and 10-min bouts. We employed analyses of covariance (ANCOVA) to assess the relationship between changes in MVPA over 12 months, calculated as a change score, and intervention assignment (intervention versus usual care). Results Participants completing both baseline and 12-month accelerometer assessments (n = 121) had a mean age of 36.1 (SD = 5.43) years and a mean body mass index of 30.24 kg/m2 (SD = 2.60). At baseline, 38% met the physical activity recommendation (150 min of MVPA/week) when assessed using 10-min bouts, and 76% met the recommendation when assessed using 1-min bouts. There were no significant differences in change in MVPA participation among participants randomized to the intervention from baseline to 12-months using 1-min bouts (adjusted intervention mean [95% CI]: 20.50 [−109.09 to 150.10] vs. adjusted usual care mean [95% CI]: -80.04 [−209.21 to 49.13], P = .29), or 10-min bouts (adjusted intervention mean [95% CI]: 7.39 [−83.57 to 98.35] vs. adjusted usual care mean [95% CI]: -17.26 [−107.93 to 73.40], P = .70). Conclusions Although prior research determined that the Shape intervention promoted weight gain prevention, MVPA did not increase significantly among intervention participants from baseline to 12 months. The classification of bouts had a marked effect on the prevalence estimates of those meeting physical activity recommendations. More research is needed to understand how to promote increased MVPA in weight gain prevention interventions. Trial registration This study is registered at www.clinicaltrials.gov database (No. NCT00938535. Retrospectively Registered 7/10/2009).